Smoking in adolescents: prevalence and 15-year trends (population surveys in Novosibirsk, 1989—2003) - D. V. Denisova; Yu. P. Nikitin; L. G. Zavyalova (Кардиоваскулярная терапия и профилактика)
Aim. To study smoking prevalence and trends in megapolis adolescents over the socio-economic transition period in Russia.Material and methods. Four population screening surveys (1989, 1994, 1999, and 2003) were performed in random representative samples of 14—17-year-old adolescent school pupils from one Novosibirsk district. In total, 2569 adolescents (1214 boys and 1355 girls) were surveyed. Attitude towards smoking was assessed in questionnaire survey; the examination protocol also included anthropometry, blood pressure measurement, blood biochemistry (lipid profile) and postal survey of parents.Results. Over 15 years, the prevalence of regular smoking (at least 1 cigarette per week) in adolescent Novosibirsk boys decreased from 45% in 1989 to до 27% in 2003 (р<0,05). On the contrary, in adolescent girls, regular smoking prevalence increased from 19% in 1989 to 27% in 2003 (р<0,05). Smoking dose remained unchanged in boys and increased in girls: from 15 cigarettes per week in 1989 to 29 in 2003 (р=0,001). Mean age of smoking initiation decreased both in boys (from 13,8 years in 1989 to 12,3 years in 2003) and girls (from 14,3 to 13,7 years, respectively). In smoking families, the percentage of adolescent smoking was twice as high as in non-smoking families: 65% vs. 35% (p<0,05). Smoking boys, especially heavy smokers, demonstrated significantly lower levels of anti-atherogenic cholesterol fractions. Hypoalphacholesterolemia prevalence was almost twice as high in regularly smoking boys as in their non-smoking peers.Conclusion. High smoking prevalence in Novosibirsk adolescents, increasing smoking rates in girls, reducing smoking initiation age and increasing smoking intensity, negative effects of smoking on anti-atherogenic cholesterol fractions in boys, smoking association with low physical activity, and negative impact of smoking families all point to the importance of adolescent smoking problem in Novosibirsk and the need for preventive action.